Facts About Economic Integration: How Integrated is New Zealand with the Rest of the World? - Vicki Plater; Megan Claridge (New Zealand Government, The Treasury, 2000)
The paper provides comparative data about New Zealand's current level of market and policy integration with the rest of the world. Market integration occurs when two or more economies function as a single market. It is likely to be evidenced by high flows of goods, services, capital and labour and convergence of prices. Policy openness and integration are means governments might use to encourage, impede or direct market integration. Indicators include lack of barriers to cross border flows and similarity or compatibility of policy settings between countries. The paper concludes that New Zealand has a relatively high level of integration with the global economy. The widespread perception, however, that New Zealand is a great deal more open and integrated than the rest of the world is not supported. We are broadly similar to other advanced economies in both openness of policies and integration of markets, and significantly less integrated than other small economies. New Zealand started opening comparatively recently. The perception that we are 'leading the bunch' may have arisen due to the rapid liberalisation required to catch up with other advanced economies and overcome the burden of distance.
Keywords: 330